Optimum sample size for Pratylenchus goodeyi (Cobb) Sher and Allen density and damage assessment in highland banana (Musa AAA) in Uganda - Speijer, P.R.; Ssango, F.; Kajumba, C.; Gold, Cliford S. (1998)
The optimum sample size for assessment of nematode densities and related damage in East African highland banana was estimated at Kikoni parish in Ntungamo district, Uganda. Kikoni parish is at an elevation ranging from 1360 to 1480 meters above sea level and the East African highland banana (Musa AAA, Matoke and Mbidde groups) is the dominant crop. The parish is approximately 10 km2 in size, with an estimated total of 500 farms. Out of these farms, 24 were randomly selected and a minimum of 15 plants per farm were sampled. Root samples were collected from recently flowered plants, assessed for root damage and nematodes were extracted from the scored root segments. Hierarchical classification analysis was performed on the values for density and damage to calculate the coefficient of variation and the method of maximum curvature was used to determine the optimum number of farms in the parish and number of banana plants within each farm for nematode density and damage assessment. Pratylenchus goodeyi was the dominant species with densities ranging from 500 to 25,000 per 100g fresh root weight, while the percentage dead roots ranged from 0.8% to 14.0% and the percentage root necrosis from 1.1% to 17.1%. The optimum numbers established, were three farms within the parish and five recently flowered banana plants in each farm.